Modern MRI diagnostics of upper-extremity-related nerve injuries - a prospective multi-center study protocol for diagnostics and follow up of peripheral nerve injuries - Aman, Martin; Schwarz, Daniel; Stolle, Annette M.; Bergmeister, Konstantin D.; Böcker, Arne Hendrik; Däschler, Simeon C.; Bendszus, Martin; Kneser, Ulrich; Harhaus-Wähner, Leila (Journal of Personalized Medicine, 2022)
(1) Background: Peripheral nerve injuries are severe injuries with potentially devastating impairment of extremity function. Correct and early diagnosis as well as regular regeneration observation is of utmost importance for individualized reconstruction and the best possible results. Currently, diagnoses and follow-up examinations are based on clinical examinations supported with electroneurography, which often causes delays in treatment and can result in impaired healing. However, there is currently no diagnostic device that can reliably correlate the anatomic-pathological parameters with the functional-pathological changes initially and during therapy. With new technologies such as MR neurography (MRN), precise visualization of potential nerve damage and visualization of the reinnervation processes is assumed to accelerate clinical decision making and accompaniment of individualized treatment. (2) Methods/Design: This prospective clinical study will examine 60 patients after peripheral nerve lesion aged 18-65 years from trauma timepoint onward. Patients should be observed over a period of 18-24 months with regular clinical examinations, electroneurography, and ultrasound to compare the potential of MRN to current gold-standard diagnostic tools. Furthermore, 20 patients with the same inclusion criteria stated above, with an internal fixation and osteosyntheses of humerus fractures, will be examined to determine the visibility of peripheral nerve structures in close proximity to metal. (3) Discussion: Peripheral nerve injuries are often accompanied with severe, expensive, and long-lasting impairment of extremity function. An early and precise diagnosis of the nerve lesion, as well as the healing course, is crucial to indicate the right therapy as soon as possible to save valuable time for nerve regeneration. Here, new technologies such as MRN aim to visualize nerve injuries on fascicular level, providing not only early diagnosis and therapy decisions, but also providing a precise tool for monitoring of reinnervation processes. As severe injuries of a nerve are often accompanied with bone fractures and internal fixation, we also aim to evaluate the visualization feasibility of nerves in close proximity to metal, and ultimately improve the outcome and extremity function of patients after a peripheral nerve injury.
Gesehen am 10.01.2023